The Influence of Intellectual Capital and Firm Size on Financial Performance of Manufacturing Companies in Indonesia - M Khoirur Rifqi; Nurhadi Nurhadi (Yayasan Riset dan Pengembangan Intelektual, 2023)
Intellectual Capital is a part of intangible assets that companies can leverage to create a competitive advantage. This research aims to examine the influence of IC (capital employed, human capital, structural capital efficiency) on financial performance with firm size as a controlling variable in manufacturing companies. The research employs an associative quantitative research method. The sample in this study consists of manufacturing companies listed on the IDX during the period 2020-2022, with a total sample of 51 companies. The sampling technique used is purposive sampling. This research utilizes secondary data from the website www.idx.com. The analysis technique involves multiple linear regression analysis using SPSS 25 software. The results of this research indicate that VACA and VAHU have a positive and significant effect on Financial Performance (ROE). Meanwhile, STVA and firm size as control variables do not exhibit a significant effect on financial performance (ROE). Previous research has identified relationships between these factors; however, this study strengthens understanding by exploring deeper complexities within them. Thus, this research makes a significant contribution to enriching the literature on company financial performance and IC.